Collaboration Paradox: Scientific Productivity, the Internet, and Problems of Research in Developing Areas - Ricardo B. Duque etal
We examine the ways in which the research process differs in developed and developing areas by focusing on two questions: First, is collaboration associated with productivity? Second, is access to the Internet (specifically use of email), associated with reduced problems of collaboration? Recent analyses by Lee and Bozeman (2004) and Walsh and Mahoney (2003) suggest affirmative answers to these questions for U.S. scientists. Based on a comparative analysis of scientists in Ghana, Kenya and the State of Kerala in southwestern India (n=918), we find that (1) collaboration is not associated with any general increment in productivity, and (2) while access to email does attenuate research problems, such difficulties are structured more by social context than by the collaborative process itself. The interpretation of these results suggests a paradox that raises issues for future studies: those conditions that unsettle the relationship between collaboration and productivity in developing areas may undermine the collaborative benefits of new information and communication technologies